2001
DOI: 10.1145/506732.506738
|View full text |Cite
|
Sign up to set email alerts
|

A systemic framework for the field of information systems

Abstract: The main aim of this paper is to present a systemic framework of what the field of Information Systems (IS) is about; its connecting areas and its central theme. It was born out of a search for structure in providing a cohesive picture of the subject and field of IS for students and business managers. The average manager and executive has difficulty in obtaining an integrated and holistic view of information systems, and it is said that this leads to a lack of alignment between IS and the strategic aims of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 37 publications
0
51
0
Order By: Relevance
“…In essence there are several issues related to over empathizing technology over social aspects, i.e. considering the whole Information System (IS), encompassing technology as well as human activities in relation to technology [6]. In trying to treat both social and technical aspects of interoperability different approaches have been taken, with Enterprise Architectures (EA) being increasingly popular [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…In essence there are several issues related to over empathizing technology over social aspects, i.e. considering the whole Information System (IS), encompassing technology as well as human activities in relation to technology [6]. In trying to treat both social and technical aspects of interoperability different approaches have been taken, with Enterprise Architectures (EA) being increasingly popular [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…They note that this distinction is already established in the general information systems (IS) literature, where there are frameworks focused on conceptual understanding of IS [4], [32] and frameworks guiding implementation [6], [22]. Likewise in the KM literature, it is possible to identify frameworks that seem to address the question of 'what is,' and to identify implementation frameworks that address the 'how to'.…”
Section: Methodological Approach To Framework Developmentmentioning
confidence: 99%
“…De Souza et al [93] promoted a semiotic approach to HCI research. For the field of information system research Bacon and Fitzgerald [94] identified a need for a systematic framework and proposed one. Ng [87] introduced a theoretical framework for understanding the relationship be-tween situated action and planned action models in the information retrieval contexts.…”
Section: A Does Hci Need a Coherent Framework?mentioning
confidence: 99%